2021
DOI: 10.3390/polym13122022
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Particles Designed for Targeted Delivery

Abstract: Pure bioactive compounds alone can only be exceptionally administered in medical treatment. Usually, drugs are produced as various forms of active compounds and auxiliary substances, combinations assuring the desired healing functions. One of the important drug forms is represented by a combination of active substances and particle-shaped polymer in the nano- or micrometer size range. The review describes recent progress in this field balanced with basic information. After a brief introduction, the paper prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 247 publications
(511 reference statements)
0
8
0
Order By: Relevance
“…Compared to unmodified starch, dextrins have improved water solubility and form solutions with lower viscosity [55]. Maltodextrin (MD) is produced by acidic and/or controlled enzymatic hydrolysis of starch and it is composed of D-glucose blocks bound by α-(1,4) and α- (1,6) bonds. It contains 2-3% glucose and 5-7% maltose.…”
Section: Preparation Of Maltodextrin Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to unmodified starch, dextrins have improved water solubility and form solutions with lower viscosity [55]. Maltodextrin (MD) is produced by acidic and/or controlled enzymatic hydrolysis of starch and it is composed of D-glucose blocks bound by α-(1,4) and α- (1,6) bonds. It contains 2-3% glucose and 5-7% maltose.…”
Section: Preparation Of Maltodextrin Microparticlesmentioning
confidence: 99%
“…Controlled-release polymer microparticles can also increase drug stability, especially in molecules that are prone to rapid degradation in the body. Such formulations are generally associated with a significant reduction in the number of applications and better patient acceptance [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nanoparticles have been proposed as one promising modality for brain drug delivery due to their advantages, including enhanced solubility of drug payload, reduced drug metabolism, biodegradability, enhanced therapeutic efficacy, and reduced toxicity relative to the administration of free drugs. , Additionally, polymeric nanoparticles can be easily engineered by tuning their physicochemical properties based on the targeted application with enhanced delivery to brain. Nevertheless, these studies are still far from optimal as the accumulation in the liver reduces the overall availability of the drug in the CNS. , One of the common ways to enhance drug delivery across the BBB is to adorn the surface of these bespoke nanomaterials with targeting ligands that can be recognized by the receptors expressed on the BBB and internalized via the process of endocytosis. , In addition to the nanoparticle size, shape, surface charge, ligand type, conjugation strategy, orientation, and ligand density have recently emerged as critical parameters that significantly dictate the mechanism and kinetics of its cellular interaction. , In a recent review article, it was demonstrated that when the ligand density increases, the cellular association increases to a limit, after which a constant or decreased association is observed . Interestingly, targeted nanoparticles often qualitatively report the ligand density as ‘low’, ‘intermediate’, and ‘high’, or as a percentage and only a few reports quantitatively determine the number of ligands per nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Among abiotic vector systems there are polymer [10], lipid [11,12], magnetic [13], and gold-based nanoparticles [12]. Such delivery systems have a number of distinct advantages, in particular, an ability to load large-sized components, ease of formation, low toxicity, minimal immune response [14][15][16].…”
Section: Introductionmentioning
confidence: 99%